2009
DOI: 10.1016/j.cell.2009.05.022
|View full text |Cite|
|
Sign up to set email alerts
|

The Tumor Suppressor Par-4 Activates an Extrinsic Pathway for Apoptosis

Abstract: Summary Prostate apoptosis response-4 (Par-4) is a pro-apoptotic protein with intracellular functions in the cytoplasm and nucleus. Unexpectedly, we noted Par-4 protein is spontaneously secreted by normal and cancer cells in culture, and by Par-4 transgenic mice that are resistant to spontaneous tumors. Short exposure to endoplasmic reticulum (ER) stress-inducing agents further increased cellular secretion of Par-4 by a brefeldin A-sensitive pathway. Secretion occurred independently of caspase activation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
203
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 232 publications
(211 citation statements)
references
References 22 publications
7
203
0
1
Order By: Relevance
“…In this model, the C-terminal region of GRP78 is expected to be exposed extracellularly. In support of this, studies using antibodies against the C terminus of GRP78 in FACS analysis detected surface GRP78 expression (18,33). Here we observed that the His epitope tagged at the C terminus of GRP78 is also exposed.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…In this model, the C-terminal region of GRP78 is expected to be exposed extracellularly. In support of this, studies using antibodies against the C terminus of GRP78 in FACS analysis detected surface GRP78 expression (18,33). Here we observed that the His epitope tagged at the C terminus of GRP78 is also exposed.…”
Section: Discussionsupporting
confidence: 56%
“…However, evidence is accumulating that the N terminus of GRP78 is also exposed on the cell surface. Thus, using antibody that targets the N-terminal region of GRP78, it was demonstrated that the interaction between surface GRP78 and extracellular Par-4 and GPI-anchored Cripto and T-cadherin could be negatively affected (29,30,33). Here using FACS analysis of ectopically expressed GRP78 bearing the FLAG epitope at the N terminus, we demonstrated directly that the N terminus of GRP78 is exposed.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…From that standpoint, activation of apoptotic pathways by inducing the expression of the tumor suppressor PAWR would be more purposeful as a therapeutic strategy. Immunocytochemical studies revealed the localization of PAWR in the ER and plasma membrane, 58 and in response to severe ER stress, it might be possible that 3-AWA-induced PAWR in the ER vicinity negatively regulates both the ER pool of BCL2 and BECN1 to suppress autophagy and simultaneously activates the mitochondrial machinery (through BAX (BCL2-associated x protein) or BAK (BCL2-antagonist/killer 1) to suppress the mitochondrial pool of BCL2, 5 and promotes CASP3-mediated apoptosis. 40 Following, we assume that 3-AWA-induced activation of PAWR would be more advantageous to control disease in the ER-stressed condition rather than blocking autophagy by inhibitors.…”
Section: Discussionmentioning
confidence: 99%